تحليل معنى الإيجاز في الكلام في تفسير آيات القرآن في سورة الإخلاص (The Meaning of Ijaz Fil Kalam In Interpreting Surah Al-Ikhlas In Holy Qur'an) - Samosir, Anggun Salsabila; Ananta, Puji Aulia (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the meaning of ijaz fil kalam (concise eloquence in speech) in interpreting the verses of the Qur’an, specifically within Surah Al-Ikhlas. The phenomenon of ijaz—a hallmark of rhetorical beauty and brevity in classical Arabic—plays a critical role in revealing profound meanings in minimal wording, especially in divine revelation. Employing a qualitative descriptive approach, this study utilizes content analysis through a library research method. The primary data source is the text of Surah Al-Ikhlas, examined through the lens of classical balaghah theory and the interpretations of authoritative exegetes such as Al-Raghib Al-Asfahani, Al-Zamakhshari, and Fakhruddin Al-Razi. Findings reveal that each verse in Surah Al-Ikhlas contains distinct forms of ijaz, including ijaz hadhf (omission), ijaz qasr (restriction), and ijaz tarkib (structure), collectively reinforcing the concept of divine oneness in a concise and impactful manner. This contributes significantly to the linguistic and theological understanding of the Qur’an, offering a basis for interpretive approaches that are more attuned to rhetorical structures. The study's implications span Islamic education, Qur’anic exegesis, and Arabic language instruction, recommending the integration of balaghah-based analysis in contemporary tafsir studies. Further research is suggested to explore ijaz in other short surahs with varied da’wah contexts.